Cryogenic Minimum Quantity Lubrication Processing Technology - ZHANG Hui-ping; REN Yi; XUE Fu-guo; LIU Ren-hang (Journal of Harbin University of Science and Technology)
An important green cutting technology called cryogenic minimum quantity of lubricant (CMQL) plays a very important role in Green Manufacturing CMQL incorporates advantages from cryogenic wind and minimal quantity of lubricant (MQL) and shows good cutting property in the cutting process CMQL can reduce the cutting force and cutting temperature and increase the lubrication effect while improving the surface quality and chip morphology Especially in the process of machining difficulttocut materials, it has unique advantages over other technologies Enterprises will not only protect environment but also make huge economic benefits by this clean cutting technology In addition, CMQL inherits the spirit of green manufacturing This technology does no harm to human health, but also minimizes environmental pollution It will become more popular in the development of Green Manufacturing and have great significance on the improvement of production efficiency, reduction of energy consumption and environment pollution.